2012
DOI: 10.1097/nne.0b013e318262abc9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Employment on Nursing Students’ Academic Performance

Abstract: As more nursing students are employed, it is essential that schools of nursing examine the relationship between student employment and academic performance. In this study, we found a statistically significant negative relationship between students who work at least 16 hours a week and academic performance, especially in high-attrition courses. Current practices in nursing education must be assessed to ensure that students who must work have every opportunity to succeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
19
0
2
Order By: Relevance
“…Consistent with previous studies, the overarching motivation for nursing students combining work and study was financial necessity (Devlin et al, ; Reyes et al, ; Salamonson et al, ). Owen et al () suggest that students work and study to provide funds to purchase textbooks and other necessities, thereby alleviating some financial stress.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with previous studies, the overarching motivation for nursing students combining work and study was financial necessity (Devlin et al, ; Reyes et al, ; Salamonson et al, ). Owen et al () suggest that students work and study to provide funds to purchase textbooks and other necessities, thereby alleviating some financial stress.…”
Section: Discussionsupporting
confidence: 79%
“…While previous international research has demonstrated the detrimental effect of excessive working on students’ academic performance (Reyes et al, ; Rochford et al, ; Salamonson et al, ), few studies have sought to understand nursing students’ motivation for and experiences of engaging in paid work while studying. Our findings illuminate how first‐year nursing students try to negotiate a balance between working, studying and living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been conducted exclusively on nursing students (2, 24, 26-30). There is still considerable controversy in terms of the effects of the aforementioned factors on students’ academic failure (27, 31-37). On the other hand, beside the sample size, sampling method, study instrument, and employed statistical tests may be related to the study population and setting (5).…”
Section: Introductionmentioning
confidence: 99%
“…The background of individuals includes various exposures to individuals or experiences while at work. Recent trends have demonstrated an increase in nursing students working while they attend nursing school [16,17]. Understanding nursing students' working backgrounds and how that impacts their stress will provide nursing educators with the ability to select a simulator based upon their students' needs.…”
Section: Nursing Students' Background Are Left In the Backgroundmentioning
confidence: 99%